Narrativas civilizatorias de la enseñanza de las matemáticas: lo que se mantiene, irrumpe y se transforma y el sujeto - Guerrero Recalde, Néstor Fernando (Revista Científica, 2019)
In the present article the results of the doctoral research project "Civilizing narratives of the teaching of mathematics in Colombia" are shown. The purpose of the study was to understand, from teacher narratives, the reasons that have led to the teaching of mathematics as a knowledge for progress in Colombia. For the analysis of the teachers' narratives, the narrative research methodology proposed by Quintero (2017) was used. Its interpretative-hermeneutic character recognizes the contextual, inductive and semantic nature of the historical narrative. The results of this investigation contribute to the reflection of how the civilizatory process of the teaching of Western mathematics, converted mathematical knowledge into hegemonic knowledge, subordinating the subject to neoliberal economic models. Faced with this position, the humanization of knowledge towards the care of the Other and of the other is raised as an alternative, in the recognition of pluralism and the diversity of cultures. In the conclusions of the study it is indicated that: in first instance, that with the education of the mathematics, it becomes evident that the formation that has been privileged in the future graduates, from the decade of the 70s is still the one of the modern mathematics, secondly, that in resistance to the movement of modern mathematics the sociopolitical perspective of mathematics education breaks out. Finally, it is concluded that at the level of the initial and continuous training of teachers there are transformations on the professional practice of teachers.